Efektivitas Buah Lerak (Sapindus Rarak Dc) dan Kulit Jeruk Kalamansi (Citrofortunella Microcarpa): Alternatif Biodeterjen Ramah Lingkungan - Meisari, Karina; Mulyati, Sri; Yusmidiarti (Jurnal Sanitasi Profesional Indonesia, 2025)
Friendly Biodetergen. Environmental pollution due to detergents is an environmental problem that needs attention. Bengkulu Province, which is one of the producers of kalamansi orange plants, does not utilize the orange peel waste produced. Calamansi orange peel contains essential oils which are used as detergent fragrances and surfactants which are not environmentally friendly can be replaced using lerak fruit which acts as a biosurfactant. This research aims to determine the most effective detergent formulation in removing stains. This research is a quasi-experimental or quasi-experimental type of research using a treatment effect design in the experimental group and comparing it with the control group. Data analysis used descriptive analysis and the Kruskal Wallis Test. The results of the Kruskal Wallis test show a P value of 0.000 <0.005 so it can be concludedthere is a significant average difference between each formulation. All formulations met the pH test standard of 8 and formulation 2 was the best formulation in the cleaning power test with a soaking time of 20 minutes. Meanwhile, the organoleptic test results were not satisfactory in terms of smell and texture. Suggestions could be to carry out the same research with different extraction materials, concentrations, extraction methods and product results. Keywords: Detergent; Lerak Fruit; Kalamansi Orange